2004
DOI: 10.1111/j.1572-0241.2004.30217.x
|View full text |Cite
|
Sign up to set email alerts
|

Miniprobe Ultrasonography for Determining Prognosis in Corrosive Esophagitis

Abstract: Endoscopic ultrasonographic images presumed to reflect the destruction of muscular layers (grades II to III), as opposed to only edema (grade I), may be associated with stricture formation. This modality can accurately visualize deep lesions in corrosive esophagitis, making it prognostically useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 8 publications
0
16
0
1
Order By: Relevance
“…In other case reports, high-resolution EUS has been used to determine the nature of esophageal stenosis prior to resection, differentiating cartilaginous from fibrotic strictures [17][18][19]. Of relevance to pediatric patients, Kamijo et al [20] showed that prognostic information could be obtained on stricture formation in the days after ingestion of corrosives. Esophagitis has not been extensively examined with EUS in children although there are a few reports in adult patients [21,22].…”
Section: Discussionmentioning
confidence: 97%
“…In other case reports, high-resolution EUS has been used to determine the nature of esophageal stenosis prior to resection, differentiating cartilaginous from fibrotic strictures [17][18][19]. Of relevance to pediatric patients, Kamijo et al [20] showed that prognostic information could be obtained on stricture formation in the days after ingestion of corrosives. Esophagitis has not been extensively examined with EUS in children although there are a few reports in adult patients [21,22].…”
Section: Discussionmentioning
confidence: 97%
“…1,2 Most of the sonographic studies in children with diseases of the esophagus use high-resolution endoscopic sonography, which has been found to be a useful imaging technique for evaluation of the thickness of the esophageal wall and mucosal and submucosal lesions and the extent of lesions involving the deeper structures of the esophagus in congenital esophageal stenosis, corrosive esophagitis, esophageal atresia, eosinophilic esophagitis, and gastroesophageal reflux. [3][4][5][6][7] However, endoscopic sonography is an invasive method for assessing the esophageal wall.…”
Section: Discussionmentioning
confidence: 99%
“…A third degree burn of the hypopharynx is a further contraindication for endoscopy [4,12,[19][20][21]. Evaluation of the esophageal wall by endoscopic ultrasound (EUS) using a miniprobe has been shown to be safe, though it does prolong examination time without showing any difference with endoscopy in predicting early complications [23,24]. The destruction of the muscular layers of the esophagus observed at EUS seems a reliable sign of future stricture formation; furthermore, ultrasound examination with a radial probe may predict the response to dilatation, which usually requires more sessions when the muscularis propria is involved at EUS.…”
Section: Investigationsmentioning
confidence: 99%
“…The destruction of the muscular layers of the esophagus observed at EUS seems a reliable sign of future stricture formation; furthermore, ultrasound examination with a radial probe may predict the response to dilatation, which usually requires more sessions when the muscularis propria is involved at EUS. In spite of these encouraging reports, the role of US examination in caustic injuries is still under evaluation [23,24].…”
Section: Investigationsmentioning
confidence: 99%